Organic food consumerism through social commerce in China. Issue 1 (7th January 2019) - Tariq, Anum; Wang, Changfeng; Tanveer, Yasir; Akram, Umair; Akram, Zubair
Abstract : Purpose: The purpose of this paper is to examine the impact of consumers' attitudes towards organic food on online impulse buying behaviour as well as the moderating effect of three website features (visual, information and navigation design) on this relationship. Design/methodology/approach: Survey data were collected via an online survey using social media platforms. A total of 653 online questionnaires were collected (response rate = 72.5 per cent) and analysed by applying exploratory and confirmatory factor analyses. The proposed hypotheses were tested through structural equation modelling. Findings: Social media forums, ratings and reviews shape Chinese consumers' attitudes towards organic food and positively influence their online impulse buying in this market. Website features are critical for disseminating information on organic food. Informative webpages featuring product quality and certification have a greater moderating effect on purchase. Information cues such as nutritional content; production and processing methods, and environmentally friendliness also influence consumers' attitudes and thus impulse buying decisions. Practical implications: Marketers should reconsider their tactics for dealing with modern consumers, as webpages should be user-friendly and visually appealing with a social learning mechanism to drive organic food consumption. Originality/value: This study bridges a gap in the literature on social commerce initiatives for developing consumers' attitudes towards organic food and online impulse buying. Further, it proposes measures that can enhance organic consumption and contributes to the literature on the importance of social factors, resulting in enhanced knowledge on the online impulse buying of organic food.